Adiponectin/AdiopR1 signal inactivation contributes to impaired angiogenesis in mice of advanced age. (15th September 2018) - Piao, Limei; Yu, Chenglin; Xu, Wenhu; Inoue, Aiko; Shibata, Rei; Li, Xiang; Nan, Yongshan; Zhao, Guangxian; Wang, Hailong; Meng, Xiangkun; Lei, Yanna; Goto, Hiroki; et al.
Abstract: Background: The mechanism by which angiogenesis declines with aging remains largely unknown. Given that the plasma levels of adiponectin (APN) are decreased in the presence of ischemic cardiovascular disease, we explore the possible mechanisms by which APN/adiponectin receptor1 (AdipoR1) axis inactivation contributes to the decline in vascular regeneration capacity in elderly animals. Methods and results: To study aging-related changes in the APN/AdipoR1 axis and its impact on ischemia-induced angiogenesis, a hindlimb ischemia model was applied to young and aged mice. Aging impaired ischemia-induced blood flow recovery. An ELISA showed that the aged mice had decreased plasma APN levels. Immunostaining showed lesser capillary formation in the aged mice. The aged ischemic muscles had decreased levels of AdipoR1, peroxisome proliferator activated receptor-γ (PPAR-γ), PPAR-γ co-activator 1α (PGC-1α), phospho-AMP-activated protein kinase α (p-AMPK-α), and B cell lymphoma-2 (Bcl-2) and increased levels of cleaved caspase-8 (C-caspase-8) and gp91phox/p22phox genes or/and proteins, nicotinamide adenine dinucleotide phosphate oxidase activity, superoxide production, and matrix metalloproteinase-2/−9 activity as well as increased numbers of infiltrated macrophages and leucocytes. In in vitro experiments, aged endothelial cells had negative changes in the levels of PPAR-γ, PGC-1α, p-AMPK-α, Bcl-2, and C-caspase-8 proteins in response to oxidative stress. Genetic interventions targeted toward APN and AdipoR1 negatively affected the targeted angiogenic protein levels in aged muscles and angiogenic actions and/or aged endothelial events. Conclusion: These findings indicate that aging can reduce angiogenesis in response to hypoxia via an impaired APN-AdipoR1-dependent mechanism that may be mediated by PPAR-γ/PGC-1α signaling inactivation in advanced age. Highlights: Aging declined vascular regeneration capacity in vivo and in vitro. Aging increased oxidative stress production and inflammatory actions and apoptosis. Aging has a negative effect on the levels of APN/AdipoR and those of the downstream targeted molecules.